Mammary fibroblasts regulate morphogenesis of normal and tumorigenic breast epithelial cells by mechanical and paracrine signals - Luehr, Inke; Friedl, Andreas; Overath, Thorsten; Tholey, Andreas; Kunze, Thomas; Hilpert, Felix; Sebens, Susanne; Arnold, Norbert; Roesel, Frank; Oberg, Hans-Heinrich; Maass, Nicolai; Mundhenke, Christoph; et al. (Cancer Letters, 2012)
Stromal factors play a critical role in the development of the mammary gland. Using a three dimensional-coculture model we demonstrate a significant role for stromal fibroblasts in the regulation of normal mammary epithelial morphogenesis and the control of tumor growth. Both soluble factors secreted by fibroblasts and fibroblast-derived modifications of the matrix compliance contribute to the regulation of epithelial cell morphogenesis. Readjustment of matrix tension by fibroblasts can even induce a phenotypic reversion of breast carcinoma cells. These data offer a basis to develop new strategies for the normalization of the tumor stroma as an innovative target in cancer therapy. © 2012 Elsevier Ireland Ltd.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Acinar morphogenesis; Breast cancer; Mammary fibroblasts; Matrix compliance; Microenvironment